Ability of the Posterior Tibial Tendon to Restore Foot Alignment in Progressive Collapsing Foot Deformity: A Computational Study. Issue 2 (April 2022) - Malakoutikhah, Hamed; Madenci, Erdogan; Daniel Latt, L.
Category: Ankle; Midfoot/Forefoot; Other Introduction/Purpose: Progressive collapsing foot deformity (PCFD) is a degenerative disorder of ligaments and tendons that encompasses a wide range of deformities, including arch height loss, hindfoot valgus, and forefoot abduction. The posterior tibial tendon (PTT) is the main active stabilizer of the arch. We hypothesize that it may become injured secondarily as it attempts to maintain foot stability when the ligaments, passive stabilizers, are attenuated. Several cadaveric studies have been conducted on the role of the PTT in PCFD, but the ability of the PTT to compensate for the loss of the ligamentous stabilizers has not been clearly characterized. We developed a high-fidelity finite element model of the foot to determine the PTT's ability to maintain foot stability when the principle ligamentous stabilizers are attenuated. Methods: The encapsulating soft tissue (EST), cartilage, and cortical and trabecular bones were reconstructed in Mimics from CT scan images of a female cadaveric foot weighing 60 kg. Tension-only spring elements were used to reflect all the ligaments in ANSYS. Bodyweight and tendon forces were applied using force vectors in the direction of their lines of action. The proximal tibia was fixed only in the vertical direction, allowing it to translate and rotate in all other degrees of freedom. Nonlinear frictional contacts were used between the EST and the ground, and between the cartilages. The flatfoot was simulated by removing all of the ligaments. We measured the foot alignment angles for the flatfoot and the foot with ruptured spring/deltoid ligament, while we gradually increased the force within the PTT. The measured angles were then compared to the intact foot to evaluate the ability of the PTT to restore foot alignment. Results: The models were validated by comparing the Meary's (MA), calcaneal pitch (CPA), hindfoot alignment (HAA), and talonavicular coverage angles (TCA) to clinically-derived values. In the flatfoot, an increase of the PTT force to approximately 700% of normal ('7 ×25.71 N=180 N') led to a nearly complete restoration of foot alignment (Fig. 1). The angles associated with arch height (MA/CPA) were restored to a lesser extent than those associated with hindfoot and forefoot alignment (HAA/TCA). For the foot with ruptured deltoid ligament, increasing force within the PTT by 500% led to a restoration of near normal hindfoot alignment (Fig. 1c). For the foot with ruptured spring ligament, the forefoot abduction was completely compensated only when the PTT force was increased to 1100% of normal (Fig. 1d). Conclusion: Almost seven times the normal PTT force is required to restore the foot to neutral alignment. Augmentation of PTT force to this extent is unrealistic. However, a lesser increase in PTT force provides partial alignment compensation. Furthermore, the restoration achieved by overloading the PTT primarily impacts the alignment of the hindfoot and forefoot rather than the arch. Because the PTT can partially restore foot alignment, it may become secondarily injured when the ligaments are torn. Strengthening of the PTT through therapeutic exercise can improve its ability to restore foot alignment and should be a cornerstone of non-operative treatment of PCFD.